STUDY ON THE EFFECT OF REINFORCEMENT RATIO ON THE N-M INTERACTION DIAGRAM OF CIRCULAR COLUMNS USING A NEW DEVELOP DIRECT COMPUTATIONAL PROCEDURE - Tavio Tavio; Indra Degree K. (Institut Teknologi Sepuluh Nopember, 2010)
The calculation of reinforcement ratio of concrete columns is very significant since the calculation will guarantee the columns ductility and reinforced efficiency. However, this calculation spent a lot of time and accuracy. Hence the manual calculation will not be efficient. On the other hand, a lot of computational programs are developed recently for civil engineering calculations. This study presents a useful computer-aided program that can be used to calculate the required longitudinal reinforcement ratio in a circular column. The code of this developed program adopts from SNI 30-2847-2002, which the reduction factors based on governed by the axial load in column capacity. As comparison the developed program also adopts ACI 318-2002, which the tensile strain that controls the reduction factor. The results from this program will be verified with PCA Column for output validity.